A Scoping Review of Sleep Disturbances in Children and Adolescents with Abdominal Pain Disorders - Friesen HJ; Singh N; Schurman JV; Deacy AD; Friesen CA; Colombo JM (Pediatric Health, Medicine and Therapeutics)
Hunter J Friesen,1 Neha Singh,2 Jennifer V Schurman,1,3 Amanda D Deacy,1,3 Craig A Friesen,1,3 Jennifer M Colombo1,3 1Department of Pediatrics, Children’s Mercy Kansas City, Kansas City, MO, USA; 2Department of Obstetrics and Gynecology, University of Kansas Medical Center, Kansas City, KS, USA; 3University of Missouri Kansas-City School of Medicine, Kansas City, MO, USACorrespondence: Jennifer M Colombo, Children’s Mercy Kansas City, 2401 Gillham Road, Kansas City, MO, 64108, USA, Email jmcolombo@cmh.eduObjective/Purpose/Aim: Sleep disturbances have been implicated as contributors to chronic pain. We undertook this review to assess the current literature regarding sleep disturbances in youth with chronic abdominal pain. We assessed studies evaluating prevalence, pathophysiology, and/or outcomes to identify gaps in knowledge and to determine whether there is an evidential basis for sleep interventions in this population.Materials and Methods: Utilizing Google Scholar, Pub Med, SCOPUS, and Embase, we searched using the terms “sleep disturbances” AND (“abdominal pain”/exp OR “abdominal pain”) AND ([adolescent]/lim OR [school]/lim). Articles were included if they contained data regarding sleep disturbance prevalence, pathophysiology, or relationships to outcome. After two independent review, 32 manuscripts were included in this review.Results: Based on their high prevalence (19– 75% of abdominal pain cohorts), there is sufficient evidence to recommend routine screening for sleep disturbances in youth with chronic abdominal pain. There is a broad range of negative physiologic and emotional effects of sleep deprivation.Conclusion: Sleep disturbances are common in youth with chronic abdominal pain. Sleep interventions are appropriate when disturbances are identified though it is not yet known the degree to which these interventions will affect the pain experience and resultant disability. Future studies should focus on evaluation of specific sleep interventions on patient outcomes.Keywords: sleep, disorders of gut-brain interaction, irritable bowel syndrome, functional dyspepsia